Teaching English as a Foreign or Second Language, Second Edition : A Teacher Self-Development and Methodology Guide - Gebhard, Jerry Greer (Book collections on Project MUSE., 2006)
Teaching English as a Foreign or Second Language, Second Edition, is designed for those new to ESL/EFL teaching and for self-motivated teachers who seek to maximize their potential and enhance the learning of their students. This guide provides basic information that ESL/EFL teachers should know before they start teaching and many ideas on how to guide students in the skills of listening, speaking, reading, and writing. It stresses the multifaceted nature of teaching the English language to non-native speakers and is based on the real experiences of teachers. (Midwest).